Kondisi Optimum Adsorpsi Ion Logam Ni2+ Oleh Silika gel-GPTMS Termodifikasi Sulfonat - Ramadhani, Dwi; Oktavia, Budhi; Kurniawati, Desy; Etika, Sri Benti (Periodic, 2024)
Silica gel is a compound that has two active sides, namely silanol (Si-OH) and siloxane (Si-O-Si) which have not been effective as adsorbents so modifications are made. Silica gel is modified using monosodium salt 4-Amino-5-hydroxy-2,7-naphthalenedisulfonic acid which is reacted first with GPTMS (glycidoxypropyltrimethoxysilane) as a connecting bridge to produce sulfonate-modified silica gel-GPTMS adsorbent. The purpose of this modification is that sulfonate-modified silica gel-GPTMS are made to adsorb Ni2+ metal ions under optimum conditions at pH, contact time and concentration. The adsorption process is carried out using the batch method by seeing how much adsorbent adsorption capacity is made against the absorption of metal ions. The characterization used is an FTIR (Fourier Transform-Infrared) spectrophotometer in the analysis of the adsorbent manufacturing process and SSA (Atomic Absorption Spectrophotometry) to see the results of metal ion absorption. The results obtained according to research that has been conducted show the adsorption of sulfonate-modified silica gel-GPTMS against the absorption of Ni2+ metal ions at optimum conditions is at pH 3 and contact time for 45 with absorption capacities of 1.5265 mg/g and 1.5826 mg/g respectively.